Language mediation during consultations between deaf patients and health care providers at Chivhu Hospital, Zimbabwe (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
This study examines the extent to which the Covid-19 pandemic exacerbated language barriers between the Deaf community and healthcare providers. Virtual interviews and focus group discussions (FGDs) with Deaf merchants and other Deaf people living in Chivhu, Zimbabwe, were used to gather data for the study. Observation and document analysis were also utilized to supplement these two approaches of data acquisition. The study used critical theory as its theoretical framework in order to better understand the communication difficulties between Deaf and Healthcare practitioners. According to the study's findings, Covid-19 had a significant impact on how Deaf people and healthcare workers interacted, which helped the Deaf population receive health services. In addition, the lack of qualified Sign Language interpreters to close the communication gap between Deaf patients and healthcare professionals made it more difficult for Deaf people to access healthcare facilities. The study suggests, among other initiatives, that during emergency crisis situations like those brought on by the Covid-19 pandemic, the Government of Zimbabwe, the health system, and various stakeholders should provide accessible information and language mediators for the Deaf.
Keywords: Covid-19; language barriers; language mediation; healthcare settings